Complete plastome of the medicinally important plant, Alstonia scholaris (Apocynaceae) - Jin, Lei (Mitochondrial DNA B Resour, 2019)
Alstonia scholaris is an evergreen tropical tree with significant medicinal values. To better understand its genetic and genomic profiles, we sequenced and assembled the completed plastome of A. scholaris. The plastome is 154,699 bp in length, consisting of a large (LSC, 85,364 bp) and a small single-copy region (SSC, 18,027 bp), which are separated by a pair of inverted repeat regions (IRs, 25,654 bp). It possesses 116 unique genes (82 protein-coding genes, 30 tRNAs, and 4 rRNAs). Phylogenetic analysis suggests that A. scholaris is sister to the clade including remaining Apocynaceae species.